Los informes de la contraloría general de la república y su incorporación al proceso penal - Machuca Espinar, Carol Graciela (2025)
The research carried out is of a non-experimental and qualitative design, within which the study of the technical principles of the control system was addressed, in merit of which it was possible to determine that the reports prepared within the context of the function of said system, must be prepared by experts in government audits. As a result of the study carried out, there are a series of actions and techniques aimed at assessing the procedures and activities that need to be examined in the entity and also the benefits obtained; therefore it is necessary that the reports issued within the framework of said activities be covered with the respective formality, within the scope of the due process of control, which guarantees the respect and observance of the rights of the entities and people; for their incorporation into the criminal process, an interrogation of the expert designated by the issuing entity is required, in attention to what is indicated in the second paragraph of article 201-A of the criminal procedure law. The presence of the expert is not for the report to be read or to be limited to ratifying it; The purpose is to defend the audit carried out through exercises of explanation and justification, both in the formal and scientific aspects of the operations carried out, the performance of contrasting activities, the results obtained and the margin of error; but it is also the opportunity to clarify obscurities or ambiguities inherent to technical language, including the opportunity to respond to the observations made by the defense, including the holding of an expert debate, in accordance with article 181° of the Criminal Procedure Code.